2015
DOI: 10.4103/0253-7176.155610
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Medical Disorders in the after Math of the Uttarakhand Disaster: Assessment, Approach, and Future Challenges

Abstract: Purpose:To present the descriptive data on the frequency of medical and psychiatric morbidity and also to discuss various pertinent issues relevant to the disaster management, the future challenges and psychosocial needs of the 2013 floods in Uttarakhand, India.Materials and Methods:Observation was undertaken by the disaster management team of National Institute of Mental Health and Neurosciences in the worst affected four districts of Uttarakhand. Qualified psychiatrists diagnosed the patients using the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…All but one of the 23 studies used a cross-sectional or repeated cross-sectional design. Furthermore, one study was qualitative, 39 two were mixed methods 42 44 and the remainder were quantitative. Crabtree 39 qualitatively explored disaster-related experiences and PTSD symptoms among community members after the 2008 Kosi River floods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All but one of the 23 studies used a cross-sectional or repeated cross-sectional design. Furthermore, one study was qualitative, 39 two were mixed methods 42 44 and the remainder were quantitative. Crabtree 39 qualitatively explored disaster-related experiences and PTSD symptoms among community members after the 2008 Kosi River floods.…”
Section: Resultsmentioning
confidence: 99%
“… 35 36 52 These differences likely contributed to the observed variation in disorder prevalence estimates. For example, Channaveerachari et al 42 reported a PTSD prevalence of 0.7% among flood-affected individuals in India, assessed by a psychiatrist using ICD-10 criteria. Alternatively, Chung et al 46 reported a PTSD prevalence of 100% after a flood exposure in Pakistan, assessed using the PTSD Diagnostic Scale screening tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females were mainly home maker and stay at home mother. Even if their married, they still have more financial insecurities compare to their husband (Channaveerachari et al 2015;Siriwardhana et al 2013).…”
Section: Association Between Socio-demographic Socio-economic and Phmentioning
confidence: 99%